Restorative Characteristics of School Gardens and Student Well-Being: Evidence from Indonesian High Schools - Rima Meslita; Tartila Tartila (AL-ISHLAH: Jurnal Pendidikan, 2026)
School-based green spaces are increasingly recognized as supportive environments for adolescent well-being, yet empirical evidence from Indonesian secondary schools remains limited. Drawing on Attention Restoration Theory (ART), this study examines how school gardens contribute to students’ psychological recovery and learning-related outcomes.This study employed a convergent mixed-methods design involving 566 high school students (aged 15–18) from SMA and MA schools in Jambi Province, Indonesia. Quantitative data were collected an online questionnaire measuring perceived restorativeness (Being Away, Fascination, Extent, Compatibility), visit patterns, and reported effects. Qualitative data were obtained from open-ended responses, interviews, and field observations of garden features. Data were analyzed using descriptive statistics, correspondence analysis with chi-square tests (α = 0.05), and thematic content analysis.Students frequently used school gardens, primarily during break times for relaxation. Perceived restorativeness was strongly associated with gardens characterized by dense vegetation, canopy shade, water elements, and supportive facilities such as seating and gazebos. Students reported reduced stress, improved mood, and clearer thinking following garden visits. Correspondence analysis confirmed significant associations between restorative characteristics and environmental features, while qualitative findings reinforced the importance of vegetation and social spaces in shaping restorative experiences.The findings support ART by demonstrating that school gardens function as everyday restorative environments that enhance emotional regulation and attentional readiness. Integrating natural and functional design elements can strengthen the role of school gardens as learning-support infrastructure.